MALIGNANT OTITIS EXTERNA – OUR EXPERIENCE - MULLAPUDI, HARINI; AV, SARASWATHI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: In this study, we aim to find out different symptoms and treatment outcomes of patients who are diagnosed with malignant otitis externa according to Levenson’s criteria, attending ENT OPD in a tertiary care hospital. Methods: This is a prospective study, conducted over 18 months from August 2018 to February 2020 in the Department of ENT, GITAM Institute of Medical Sciences and Research, Visakhapatnam. Patients typically presented with nocturnal otalgia, persistent otorrhea, hearing loss, and aural fullness. Consent from patients for participation in the study has been taken. Complete history and thorough clinical examination were made, along with relevant investigations. Results: Out of the 15 patients selected, MOE is more common in males (60%) than females (40%). The most common organism isolated is Pseudomonas aeruginosa. Nocturnal otalgia was the presenting complaint in all the patients. The age group commonly affected with MOE is 60−75 years. Facial nerve palsy is seen among 46% of the patients. Dry moping and application of betadine wick after the scrapping of granulations and reasonable glycemic control was helpful in-patient recovery in 50% of the cases. Conclusion: Malignant otitis externa (MOE) is an aggressive infection representing a life-threatening condition. In our patients, a prolonged topical and oral antibiotic treatment and strict control of glycemic levels permitted to control the disease, but the surgical approach by debridement of granulations appeared essential for the resolution of the disease.